TECHNOLOGY MANAGEMENT IN GENETICS - Hatairuk Tungkasen, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
Technology management in genetics course utilizes laboratory techniques and instrumentation to study the genetics involves the molecular genetics such as DNA, RNA or protein. Specifically, the variety of technologies methods to suit different learning styles including media or video bring benefits and the knowledge base is important to develop the learner. This research has been shown the technology of genetics to teach and learning for science by using videos, demonstrations and the journal of protein analysis which is SDS-PAGE technique used. Result shown the technologies management method is good to be applied for students in the course of genetics. After the student watched media, video and demonstrations the SDS-PAGE technique they can use the SDS-PAGE to analysis the proteins. The result has shown that the protein patterns from different follicle sizes. The porcine follicles ranged from 1-2 and 3-4 millimeters (mm.) follicles. As a result, showed protein patterns composed of 18 to ≥ 220 kDa which were found in follicle samples from all sizes. Moreover, the notification of the porcine follicles in diameter of 3-4 mm. has been found the protein bands at 100 and 120 kDa, in accordance to a study by Miyamoto et al., 1985 which report 100 kDa was Inhibin. The study of Nagyova in 2004 found that the protein band of 120 kDa was inter alpha trypsin inhibitor family. The information of proteins can collect in to computer system which is able to use to develop technology genetics applications for protein studies. This research shows that technologies’ management will support and have benefits for the learners. They can improve their learning and scientific skills. In the other hands, the development of new instruction media and teaching techniques are important and necessary for continuing works through the scientific process systematically